2022
DOI: 10.3389/fcell.2021.727595
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression-Based Predication of RNA Pseudouridine Modification in Tumor Microenvironment and Prognosis of Glioma Patients

Abstract: Aberrant expression of methyltransferases and demethylases may augment tumor initiation, proliferation and metastasis through RNA modification, such as m6A and m5C. However, activity of pseudouridine (Ψ) modification of RNA remains unknown in glioma, the most common malignant intracranial tumor. In this study, we explored the expression profiles of the Ψ synthase genes in glioma and constructed an efficient prediction model for glioma prognosis based on the CGGA and TCGA datasets. In addition, the risk-score s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Importantly, the association between high S100A11 gene expression and poor survival outcomes has been previously shown across all breast cancer subtypes [41,42]. In agreement with our findings on cancer-macrophage crosstalk in ER+ breast cancer, a previous study employed bulk transcriptomics in glioblastoma and found that high expression of S100A11 predicted high infiltration of multiple immune cell types, including macrophages [43]. Another glioblastoma study used scRNA-seq analysis to independently confirm that S100A11-high cancer cells are associated with higher immune cell numbers [44].…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the association between high S100A11 gene expression and poor survival outcomes has been previously shown across all breast cancer subtypes [41,42]. In agreement with our findings on cancer-macrophage crosstalk in ER+ breast cancer, a previous study employed bulk transcriptomics in glioblastoma and found that high expression of S100A11 predicted high infiltration of multiple immune cell types, including macrophages [43]. Another glioblastoma study used scRNA-seq analysis to independently confirm that S100A11-high cancer cells are associated with higher immune cell numbers [44].…”
Section: Discussionsupporting
confidence: 91%
“…Pseudouridylation, in particular, is known to be the most abundant modification in total RNA from human cells, but the effect of Pseudouridylation is still poorly understood. Previous studies have shown that RNA pseudouridine modification could affect the prognosis of glioma patients by enriching tumour-infiltrating immune cells such as macrophages M0 and Tregs (32). Dyskerin pseudouridine synthase 1 (DKC1), a gene located on the X chromosome, is associated with the progression of multiple diseases (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to T cells and B cells, most studies on m 5 C RNA modifications in macrophages are in the context of cancer development, especially macrophage infiltration in the TME. The risk scores based on m 5 C-related genes of patients with four types of cancer (HCC, HNSCC, glioma and pancreatic cancer) were positively correlated with infiltration of resting macrophages (M0), M1 or M2 macrophages ( 138 , 147 , 148 , 156 , 159 ). Analysis of the TME in prostate cancer patients showed differentially expressed NSUN6, TET1 and TET3 in M1 and M2 macrophages ( 38 ).…”
Section: C Rna Modification In Immune Cellsmentioning
confidence: 99%
“…Recent studies have mainly focused on the m 5 C RNA modification of T cells in the context of cancer. For instance, the abundance of CD4+ T cells is higher in patients with soft tissue sarcoma (STS) ( 149 ), ccRCC ( 110 ) and HCC ( 148 ) but the opposite is found in glioma patients ( 156 ). Tregs appear to be slightly different from common CD4+ T cells, as they correlate with poor prognosis in STS ( 149 ) and HCC ( 138 ) patients and positive outcomes in HNSCC ( 147 ) and bladder cancer ( 140 ) patients.…”
Section: C Rna Modification In Immune Cellsmentioning
confidence: 99%